The Role of Ukrainian Studies in Ukraine's National Security and Exposing Russian Fakes - Fihurnyi, Yuriі; Shakurova, Olha (Skhid : analitychno-informat͡s︡iĭnyĭ z͡h︡urnal, 2025)
The article analyzes the role of Ukrainian Studies in Ukraine's national security and the exposing of Russian fakes. It has been found that the Russo-Ukrainian War has become a huge challenge for Ukraine and Ukrainians, as it is being waged not only by military (conventional) means but also through information warfare and propaganda. It is revealed that Russian aggressors (Rashists) are attempting to defeat Ukrainian citizens not only on the battlefield but also in the information space, promoting a "Rashist" worldview and convincing Ukrainians of their inferiority. They also impose Putin’s ideology of the "Russian World" and imperial myths about the "single people," "blood brothers – Russians and Ukrainians," and similar narratives on the Ukrainian nation, thereby attempting to restore the USSR 2.0 in the format of "Great Historical Russia." It is shown that Russian myths are utilized as a powerful tool of hybrid warfare to falsify historical events, create false ideas about socio-political reality, and form a false social reality for the objects of information influence. As a result of these systemic actions, Ukraine's national security faces the threat of significant weakening. It is emphasized that Ukrainian Studies, as an interdisciplinary integrative science and an independent educational discipline, possesses great potential and real opportunities to actualize the intellectual achievements of Ukraine’s humanitarian elite to strengthen national security, reinforce national identity, and refute the propaganda myths and fakes of the Russian aggressors (Rashists). It is demonstrated that an important component of strengthening Ukraine's national security and national identity, and refuting Russian myths, is the creation of an appropriate legal framework that will enhance legal support for countering Russian propaganda narratives. It is established that Ukrainian Studies in the 20th and early 21st centuries contributes to the strengthening of Ukrainian national identity in Ukraine as a vital part of national security, thereby actualizing Ukrainian ethnic formation, state formation, nation formation, and ethno-cultural formation. It is concluded that Ukrainian Studies can become the national and worldview ideology of the Ukrainian Independent United State.